String-Inspired Correction to R2 Inflation - Ekaterina Pozdeeva; Sergei Ketov; Sergey Vernov (Physical Sciences Forum, 2023)
We study the Starobinsky–Bel–Robinson inflationary model in the slow-roll regime. In the framework of higher-curvature corrections to inflationary parameters, we estimate the maximal possible value of the dimensionless positive coupling constant <semantics>β</semantics> coming from M-theory.